Analyzing Gerrit Code Review Parameters with Bicho - Gonzalez-Barahona, Jesus; Izquierdo-Cortazar, Daniel; Robles, Gregorio; del Castillo, Alvaro (Electronic Communications of the EASST, 2014)
Code review is becoming a common practice in large scale software development projects. In the case of free, open source software projects, many of them are selecting Gerrit as the system to support the code review process. Therefore, the analysis of the information produced by Gerrit allows for the detailed tracking of the code review process in those projects. In this paper, we present an approach to retrieve and analyze that information based on extending Bicho, a tool designed to retrieve information from issue tracking systems. The details of the retrieval process, the model used to map code review abstractions to issue tracking abstractions, and the structure of the retrieved information are described in detail. In addition, some results of using this approach in a real world scenario, the OpenStack Gerrit code review system, are presented.